The Gender in Stories: How War Stories and Police Narratives Shape Masculine Police Culture - Kurtz, Don L. (Women & criminal justice, 2018)
This research examines storytelling and narrative development in police culture related to gendered aspects of policing. Interviews with 28 officers indicates that women are frequently viewed through a gendered lens and that police storytelling appears an important context for understanding police culture. The types of stories explored in this paper-flow of action, war stories, and gender narratives-provide a context for understanding the (re)production of masculinity in policing. By paying close attention to police narratives we can gain insight into the maintenance of masculine police culture. The findings also build on the growing foundation of narrative inquiry in criminology.